(untitled) (Global Scientific Review, 2023)
Properly organized education for the child, the character of the interaction of the family and its members, social groups in which the child communicates, the profession he chooses, such as the perfection of the child’s inner mental capabilities a number of social and biological factors do not necessarily have an impact on the formation of personality, self-awareness and attitude towards others and its intellectual progress.